2020
DOI: 10.1519/jsc.0000000000003939
|View full text |Cite
|
Sign up to set email alerts
|

Step vs. Two-Phase Gradual Volume Reduction Tapering Protocols in Strength Training: Effects on Neuromuscular Performance and Serum Hormone Concentrations

Abstract: Sepp änen, S and H äkkinen, K. Step vs. two-phase gradual volume reduction tapering protocols in strength training: Effects on neuromuscular performance and serum hormone concentrations. J Strength Cond Res 36(10): 2771-2779, 2022-This study assessed effects of 2 reduced volume tapering protocols on neuromuscular performance and serum hormone concentrations in 14 recreationally strength-trained men (21-30 years). After an 8-week strength training period subjects were divided to the step (54% volume reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The initial 4 weeks of training were followed by a 1-week planned overreach (150% of the total volume relative to the initial 4 weeks) and a 1-week step-taper (50% of the total volume relative to the planned overreach). A 50% reduction in volume during a step-taper has been consistently reported in the literature and aligns with the recommendations of recent reviews (i.e., 30–70% volume reduction) (31,33,36,38,40). In addition, a 1-week overreach directly preceding a taper has previously been shown effective in strength and power athletes (3,5,40).…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…The initial 4 weeks of training were followed by a 1-week planned overreach (150% of the total volume relative to the initial 4 weeks) and a 1-week step-taper (50% of the total volume relative to the planned overreach). A 50% reduction in volume during a step-taper has been consistently reported in the literature and aligns with the recommendations of recent reviews (i.e., 30–70% volume reduction) (31,33,36,38,40). In addition, a 1-week overreach directly preceding a taper has previously been shown effective in strength and power athletes (3,5,40).…”
Section: Methodssupporting
confidence: 87%
“…This has been previously identified as a limitation in the current literature surrounding tapering and training cessation (37). However, recent research has experimentally compared different tapering protocols (29,33,40). Notably, Travis et al (40) demonstrated a 1-week step-taper and a 3-week exponential taper to improve 1RM BS and BP similarly, whereas 1RM DL improved only in the exponential group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations